MECHANICS OF LANDSLIDE INITIATION AS A SHEAR FRACTURE PHENOMENON - Martel S.J. (My University, 2004)
A 3-D model of shear fracture in an elastic half-space provides insight into the initiation of sliding along weak pre-existing surfaces in rock or consolidated sediments. An elastic model is justified physically if regions of non-elastic deformation associated with sliding are small relative to the size of the shear fracture. A subsurface elliptical shear fracture parallel to the surface simulates sliding at depth along a pre-existing weakness (e.g. a bedding plane). Based on the stress concentration at the shear fracture perimeter, the model predicts landslide scars will tend to have elliptical shapes in map view and width-to-length values of 0.5-1, consistent with many observations. As a shear fracture spreads, the stress concentration at its perimeter promotes its propagation up towards the surface. The model predicts that sliding at depth causes and precedes fracturing at the surface. For a shear fracture less then twice as long as it is wide, surficial fracturing should start in the head and from there 'unzip' down along the slide flanks. Depending on the ambient stress state and the shear strength loss at the slide base, a shear fracture might need to become several or more times wider and longer than its depth to develop a sufficiently intense stress concentration to propagate out of plane to the surface. This accounts for the large length-to-thickness ratios of many natural slides. The model also accounts for the following generic landslide characteristics: a steep, arcuate, concave-downhill head scarp; an echelon pattern of opening-mode fractures along the flanks and subparallel to the head scarp trace; subsidence and normal faulting near the head of a slide; and uplift with thrust faulting near the slide toe.
Keywords: LANDSLIDES; SUBMARINE LANDSLIDES; MECHANICS; FRACTURES; ELASTICITY